Origins, destinations and catchments: mapping travel to work in Ireland in 2002 - Walsh, Jim; Foley, Ronan; Kavanagh, Adrian; McElwain, Ashling (Statistical and Social Inquiry Society of Ireland, 2006)
Over recent years there has emerged an increased awareness of the importance of strategic spatial planning and of the extent to which concepts such as place and space really matter. An enhanced understanding of the geography of living and of the economy requires not only a knowledge of where people and objects are but also of how those places relate to one another. This requires fundamentally sound data on movement patterns, of which the most important is probably the daily journey to work (Horner, 1999). In this paper we explore for the first time several aspects of the journey to work using data from the CSO 2002 Census of Population (CSO 2003a, CSO 2003b. CSO 2004a). While the approach at this stage is mainly descriptive supported by detailed mapping it is timely and it will hopefully contribute to discussion in a number of areas of public policy. These include the estimation of regional per capita levels of output (per capita GVA), the extent of the catchment areas of the National Spatial Strategy Gateways and hubs, the environmental sustainability of new trip patterns, and the impact of longer and more stressful journey times on quality of life.
Read before the Society, 20 October 2005
Keywords: Catchment areas; Commuting; Spatial planning; 314.15